2022
DOI: 10.4193/rhin21.446
|View full text |Cite
|
Sign up to set email alerts
|

Individual symptom visual analogue scale severity scores for determining EPOS guideline-based chronic rhinosinusitis disease control

Abstract: Background: The goal of this study was to determine how to translate visual analogue scale (VAS) symptom scores to the binary, descriptive symptom scales used in the European Position Paper on Rhinosinusitis and Nasal Polyps (EPOS) criteria for chronic rhinosinusitis (CRS) disease control. Methods: 309 CRS patients were recruited. All patients rated their burden of 5 symptoms (nasal blockage, rhinorrhea/postnasal drip, facial pain/pressure, smell loss, sleep disturbance or fatigue) using the binary EPOS descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…14 A total of two hundred patients' deidentified data were chosen from a previously described dataset used to study CRS disease control. 12 Other than to represent data from patients who reported their CRS disease control as "controlled" versus "partly controlled" versus "uncontrolled" as evenly as possible, patient data was randomly chosen. A total of 15 rhinologists were recruited to be able to detect a difference of large effect size in the agreement between rhinologistassessed CRS control and patient-reported CRS control from the first data set (when patient-reported CRS control was provided) and the second data set (when patientreported CRS control was not provided) with a power of 0.8 and with a significance of 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14 A total of two hundred patients' deidentified data were chosen from a previously described dataset used to study CRS disease control. 12 Other than to represent data from patients who reported their CRS disease control as "controlled" versus "partly controlled" versus "uncontrolled" as evenly as possible, patient data was randomly chosen. A total of 15 rhinologists were recruited to be able to detect a difference of large effect size in the agreement between rhinologistassessed CRS control and patient-reported CRS control from the first data set (when patient-reported CRS control was provided) and the second data set (when patientreported CRS control was not provided) with a power of 0.8 and with a significance of 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…These deidentified patient data were taken from a previous study in which the CRS symptom severities were collected from patients using the same dichotomous scales for the EPOS CRS control criteria, and in which patients also rated their own CRS disease control on a scale of "controlled," "partly controlled," or "uncontrolled." 12 Based on the EPOS disease control criteria and patientreported CRS control, participating rhinologists were asked to classify each patient's CRS disease control on a scale of "controlled," "partly controlled," and "uncontrolled," which is consistent with the EPOS disease control classifications and guideline classifications of asthma control. 5,13 Participating rhinologists were specifically instructed that CRS control was defined as the extent to which CRS manifestations were within acceptable limits and that CRS control serves as the goal of treatment, with the corollary that a rating of partly controlled or uncontrolled CRS implied that the rhinologist would consider treatment change or escalation in proportion to the lack of control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2020 EPOS CRS control guidelines also proposed the possibility of dichotomizing symptom criteria based on a corresponding visual analogue scale (VAS) symptom severity score of 5 or less vs. more than 5 (on a scale of 0-10) based on inference from previous work that did not directly address the conversion of VAS symptom severity scores to descriptive symptom criteria [1,9]. More recent work and direct study of the issue has demonstrated that the dichotomization of VAS symptom severity scores as less than 3.5 vs. at least 3.5 (on a scale of 0-10) better corresponds to the descriptive symptom criteria of the EPOS CRS control guidelines [10].…”
Section: Key Pointsmentioning
confidence: 99%